FRACTAL ANALYSIS AS A METHOD OF MORPHOMETRIC STUDY OF THE HUMAN CEREBELLUM WHITE MATTER - Степаненко А. Ю.; Мар'єнко Н. І. (World of Medicine and Biology, 2016)
Fractal analysis is used to describe the structures with fractal properties – self-similarity and scale invariance. An algorithm for the use of fractal analysis for the study of the white matter of the vermis of the human cerebellum is described. The box counting method for the fractal dimension is used. Differences of white matter structure affect the value of the fractal index. A study of the white matter using fractal index can serve as a basis for the development of objective criteria for the diagnosis of age-dependent changes and atrophic diseases of the cerebellum.